Knowledge Structure and Research Evolution of Organizational Support Perception, Job Satisfaction, and Organizational Citizenship Behavior: Bibliometric Analysis - Nasution, Cecilia Stephani Permatadewi; Widhiastuti , Hardani; Dewi , Rusmalia (Journal Corner of Education, Linguistics, and Literature, 2025)
This study examines the intellectual structure and research evolution concerning Perceived Organizational Support, Job Satisfaction, and Organizational Citizenship Behavior within the domain of organizational psychology. The study aims to identify dominant themes, conceptual relationships, and emerging trends in the literature related to these constructs. The data set consisted of 124 scientific publications retrieved from the Scopus database using predefined inclusion and exclusion criteria and a systematic screening procedure. The research employed a qualitative approach with a Systematic Literature Review design combined with bibliometric analysis. Data collection was conducted through structured database queries, while data analysis utilized Vosviewer to visualize keyword co-occurrence, thematic clusters, and research development patterns. The findings reveal that Perceived Organizational Support, Job Satisfaction, and Organizational Citizenship Behavior represent central and consistently interconnected themes in the literature. Several supporting constructs, including commitment, trust, organizational justice, and relational dynamics, were also identified as integral components of the conceptual network. Overlay and density visualizations indicate that the field demonstrates a stable yet evolving research trajectory, with the integration of contemporary variables without displacing foundational constructs. The study concludes that these three constructs remain theoretically and empirically significant within organizational psychology and contribute to understanding positive workplace behavior. The implications of this study emphasize the importance of organizational and psychological factors in shaping employee attitudes and discretionary behaviors.